Resilience Among Parents of Adolescents With Type 1 Diabetes: Associated With Fewer Parental Depressive Symptoms and Better Pediatric Glycemic Control - Luo, Dan; Wang, Yubing; Cai, Xue; Li, Ruxue; Li, Mingzi; Liu, Haiyan; Xu, Jingjing (Frontiers in Psychiatry, 2022)
Background Although pediatric resilience plays a significant role in resisting negative moods and improving glycaemic control, little research exists regarding resilience among the parents of adolescents with Type 1 diabetes. Objective To investigate parental resilience's correlations with parental depressive symptoms, parental diabetes distress, and pediatric glycaemic control. Methods This cross-sectional study recruited adolescents with Type 1 diabetes and their parents from two hospitals. The parents completed questionnaires. The 10-item Connor-Davidson Resilience Scale measured resilience; the Problem Areas in Diabetes Survey-Parent Revised version measured diabetes distress; the Patient Health Questionnaire-9 measured depressive symptoms. Standard glycated hemoglobin tests were performed on the adolescents. Results Data from 224 parents (77.2% female, Mage = 39.88 [SD = 5.02], age range = 30–56 years) of adolescents (50.9% boys, Mage = 13.54 years [SD = 2.48], age range = 10–19 years) were available. More than half (52.7%) of parents exceeded the criterion score for high resilience. Parental resilience was significantly negatively associated with parental depressive symptoms and diabetes distress. Parents from the high-resilience group reported fewer depressive symptoms than those from the low-resilience group. In multivariate regressions, greater parental resilience is consistently related to better pediatric glycaemic control beyond parental psychological risk factors. Conclusions This study highlights the importance of parental resilience for parental mental health and glycaemic control among adolescents with Type 1 diabetes. The appropriate resilience support programme might be developed for parents, especially for those existing depressive symptoms and diabetes distress.